2012
DOI: 10.1159/000335996
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dopaminergic Personality Patterns in Patients with Prolactinomas: A Comparison with Nonfunctioning Pituitary Adenoma Patients and Age- and Gender-Matched Controls

Abstract: Introduction: Personality patterns such as extraversion and novelty seeking have been associated with an altered dopaminergic activity in healthy subjects. Patients with prolactinomas have been described as exhibiting an altered dopaminergic tone and are often treated with dopamine agonists. Little is known about the personality traits of this patient group. Hence, we aimed at examining whether patients with prolactinomas exhibit modified personality patterns compared to patients with nonfunctioning pituitary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Also for Cushing's disease, many studies have stressed that depression and anxiety-related personality disorders are common comorbidities in these patients (17,18,19,20,21). Patients with prolactinomas seem to experience increased neuroticism, high fear of uncertainty, and also increased fatigability and asthenia (22), but further studies are lacking. For patients with NFPAs, such data are still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Also for Cushing's disease, many studies have stressed that depression and anxiety-related personality disorders are common comorbidities in these patients (17,18,19,20,21). Patients with prolactinomas seem to experience increased neuroticism, high fear of uncertainty, and also increased fatigability and asthenia (22), but further studies are lacking. For patients with NFPAs, such data are still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CD are frequently affected by major psychiatric disorders such as depression, anxiety and psychosis, even after long-term biochemical cure of the disease (8,9). Besides, there is an increased prevalence of affective disorders or anxiety-associated personality traits in patients with acromegaly and prolactinomas (10,11). Interestingly, patients with NFPA exhibited a comparable personality pattern, potentially as a result of the pituitary lesion and/or associated hormonal dysregulations (12).…”
Section: Introductionmentioning
confidence: 99%
“…19,[85][86][87] Gonadal dysfunction is one of the most important problems in these patients. In men, decreased libido, erectile dysfunction and poor seminal fluid quality are frequent consequences of prolactin hypersecretion.…”
Section: Prolactinomasmentioning
confidence: 99%
“…In particular, prolactinoma patients presented minor extraversion, lesser novelty seeking, increased shyness and neuroticism compared with healthy controls. 87 Moreover, it has been shown that women treated for microprolactinomas were more vulnerable to anxiety and depression symptoms than control subjects. 86 Psychological support and psychiatric treatment may prevent and resolve these problems, since mental health is a major factor in perception of QoL.…”
Section: Prolactinomasmentioning
confidence: 99%